MAYBE Initial complexity problem: 1: T: (1, 1) f1(a, b, c, d, e, f) -> f2(g, g, c, d, e, f) (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f300(a, b, c, d, e, g) [ c >= d ] start location: f1 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (1, 1) f1(a, b, c, d, e, f) -> f2(g, g, c, d, e, f) (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, e, f) with all transitions in problem 2, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] We thus obtain the following problem: 3: T: (1, 2) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] with all transitions in problem 3, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] We thus obtain the following problem: 4: T: (1, 3) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] with all transitions in problem 4, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] We thus obtain the following problem: 5: T: (1, 4) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] with all transitions in problem 5, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] We thus obtain the following problem: 6: T: (1, 5) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] with all transitions in problem 6, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] We thus obtain the following problem: 7: T: (1, 6) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] with all transitions in problem 7, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] We thus obtain the following problem: 8: T: (1, 7) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] with all transitions in problem 8, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] We thus obtain the following problem: 9: T: (1, 8) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] with all transitions in problem 9, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] We thus obtain the following problem: 10: T: (1, 9) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] with all transitions in problem 10, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] We thus obtain the following problem: 11: T: (1, 10) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] with all transitions in problem 11, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] We thus obtain the following problem: 12: T: (1, 11) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] with all transitions in problem 12, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] We thus obtain the following problem: 13: T: (1, 12) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] with all transitions in problem 13, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] We thus obtain the following problem: 14: T: (1, 13) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] with all transitions in problem 14, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] We thus obtain the following problem: 15: T: (1, 14) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] with all transitions in problem 15, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] We thus obtain the following problem: 16: T: (1, 15) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 By chaining the transition f1(a, b, c, d, e, f) -> f2(g, g, c, d, g'', f) [ d >= c + 1 ] with all transitions in problem 16, the following new transition is obtained: f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] We thus obtain the following problem: 17: T: (1, 16) f1(a, b, c, d, e, f) -> f2(g, g, c, d, g', f) [ d >= c + 1 ] (?, 1) f2(a, b, c, d, e, f) -> f2(a, b, c, d, g, f) [ d >= c + 1 ] start location: f1 leaf cost: 1 Complexity upper bound ? Time: 0.992 sec (SMT: 0.925 sec)